An Inquiry Model for Mathematics Teachers’ Professional Development - Nguyen, Danh Nam (H. : ĐHQGHN, 2017)
This paper proposes an inquiry model for improving the teaching of mathematics based on the practice of lesson study. This model provides both pre-service and in-service mathematics teachers with multiple pathways for designing a mathematics lesson plan. The result of this research playsan important role in determining if the model is effective in helping teachers to develop their professional expertise. The model also leads to teachers’ improved teaching and provides valuable insightsinto the process of mathematics teaching